2012
DOI: 10.1142/s0219720012410053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Context-Dependent Errors for Illumina Sequencing

Abstract: The new generation of short-read sequencing technologies requires reliable measures of data quality. Such measures are especially important for variant calling. However, in the particular case of SNP calling, a great number of false-positive SNPs may be obtained. One needs to distinguish putative SNPs from sequencing or other errors. We found that not only the probability of sequencing errors (i.e. the quality value) is important to distinguish an FP-SNP but also the conditional probability of \correcting" thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
(7 reference statements)
3
24
0
Order By: Relevance
“…This finding was supported by Abnizova et al [81], where the authors found similar regions with similar motifs associated with high error rate. It was suggested that the origin of this artefact is the motif 's vulnerability for Illumina HiSeq common error tendencies: Cross-talk, phasing inaccuracy and G-quenching.…”
Section: Platform-specific Biasessupporting
confidence: 66%
See 4 more Smart Citations
“…This finding was supported by Abnizova et al [81], where the authors found similar regions with similar motifs associated with high error rate. It was suggested that the origin of this artefact is the motif 's vulnerability for Illumina HiSeq common error tendencies: Cross-talk, phasing inaccuracy and G-quenching.…”
Section: Platform-specific Biasessupporting
confidence: 66%
“…Sequencing errors is a challenge for aligners [48,[79][80][81]. Obviously, if a read contains more mismatches than allowed by aligner (e.g.…”
Section: Box 4: Brief Description and Classification Of Ngs Aligners mentioning
confidence: 99%
See 3 more Smart Citations